Evaluation of embedded buckypaper sensors in composite overwrappedped pressure vessels for progressive damage monitoring. (15th March 2022) - Wang, Xiaoqiang; Lin, Lunyang; Lu, Shaowei; Zhang, Lu; Li, Bohan; Zhang, Dongxu; Luo, Yongjian
Abstract: Composite overwrapped pressure vessel (COPV) with their excellent specific properties and fatigue resistance are used for high-pressure storage in aerospace industries. To predict the life of COPV and avoid disasters, carbon nanotubes have been used as buckypaper (BP) sensors embedded in COPV for permanently monitoring damage in hydrostatic pressure tests and hydraulic fatigue tests. The changes in resistance measured by BP sensors are compared with the strain changes measured by strain gages. The experimental results show BP sensors are more sensitive and reliable to the initiation and propagation of microcrack and slight stiffness degradation in COPV than strain gauges. Embedding the BP sensors into COPV is effective for real-time structural health monitoring.